The Effect of Police Body-Worn Cameras on Use of Force and Citizens’ Complaints Against the Police: A Randomized Controlled Trial - Ariel, Barak (Journal of quantitative criminology, 2015)
Objective Police use-of-force continues to be a major source of international concern, inviting interest from academics and practitioners alike. Whether justified or unnecessary/excessive, the exercise of power by the police can potentially tarnish their relationship with the community. Police misconduct can translate into complaints against the police, which carry large economic and social costs. The question we try to answer is: do body-worn-cameras reduce the prevalence of use-of-force and/or citizens’ complaints against the police? Methods We empirically tested the use of body-worn-cameras by measuring the effect of videotaping police–public encounters on incidents of police use-of-force and complaints, in randomized-controlled settings. Over 12 months, we randomly-assigned officers to “experimental-shifts” during which they were equipped with body-worn HD cameras that recorded all contacts with the public and to “control-shifts” without the cameras (n = 988). We nominally defined use-of-force, both unnecessary/excessive and reasonable, as a non-desirable response in police–public encounters. We estimate the causal effect of the use of body-worn-videos on the two outcome variables using both between-group differences using a Poisson regression model as well as before-after estimates using interrupted time-series analyses. Results We found that the likelihood of force being used in control conditions were roughly twice those in experimental conditions. Similarly, a pre/post analysis of use-of-force and complaints data also support this result: the number of complaints filed against officers dropped from 0.7 complaints per 1,000 contacts to 0.07 per 1,000 contacts. We discuss the findings in terms of theory, research methods, policy and future avenues of research on body-worn-videos.